Management of Athlete Achievement Development for Sport Supaya Sehat Football School in Semarang City - Ihsan Rizki Prabowo; Bambang Priyono; Sri Sumartiningsih (Journal of Physical Education and Sports, 2022)
The process of fostering sports achievement is influenced by many factors, including clear coaching objectives, systematic training programs, and appropriate training materials and methods. In addition, it is necessary to consider the characteristics of the athletes being coached, both physically and psychologically, the coaches' abilities, facilities, and infrastructure, as well as the conditions of the coaching environment. The aim of the study was to analyze management, training programs, infrastructure, and funding for the 14-year-old group of SSS football schools in Semarang City. This research is a qualitative descriptive study. The approach used is the management function of Planning, Organizing, Actuating, and Controlling (POAC) by integrating the 5M elements of management resources (Man, Money, Material, method, and machine). Data collection techniques include interviews, observation, and documentation, while the research subjects are trainers, administrators, and athletes. The results showed that there were still multiple tasks in the management due to limited resources; the periodization of the training program was not quite right so that the peak performance of students was not as expected; they had not carried out a routine inventory of infrastructure; and they had not implemented tolerance beyond the policy for students who had not paid tuition fees. Conclusions Suggestions Management formulates the latest Standard Operating Procedures and implements them with full integrity. Trainers are obliged to carry out training programs that are appropriate to the program, carry out inventories, and add the latest training infrastructure to support progress in achievement. Management must be more assertive regarding payment policies Education Development Contribution.